Assessment of Bioenergetic Deficits in Patients With Parkinson Disease and Progressive Supranuclear Palsy Using 31P-MRSI. (13th December 2022) - Prasuhn, Jannik; Göttlich, Martin; Ebeling, Britt; Kourou, Sofia; Gerkan, Friederike; Bodemann, Christina; Großer, Sinja S.; Reuther, Katharina; Hanssen, Henrike; Brüggemann, Norbert
Abstract : Background and Objective: Bioenergetic disturbance, mainly caused by mitochondrial dysfunction, is an established pathophysiologic phenomenon in neurodegenerative movement disorders. The in vivo assessment of brain energy metabolism by 31 phosphorus magnetic resonance spectroscopy imaging could provide pathophysiologic insights and serve in the differential diagnosis of parkinsonian disorders. In this study, we investigated such aspects of the underlying pathophysiology in patients with idiopathic Parkinson disease (PwPD) and progressive supranuclear palsy (PwPSP). Methods: In total, 30 PwPD, 16 PwPSP, and 25 healthy control subjects (HCs) underwent a clinical examination, structural magnetic resonance imaging, and 31 phosphorus magnetic resonance spectroscopy imaging of the forebrain and basal ganglia in a cross-sectional study. Results: High-energy phosphate metabolites were remarkably decreased in PwPD, particularly in the basal ganglia (−42% compared with HCs and −43% compared with PwPSP, p < 0.0001). This result was not confounded by morphometric brain differences. By contrast, PwPSP had normal levels of high-energy energy metabolites. Thus, the combination of morphometric and metabolic neuroimaging was able to discriminate PwPD from PwPSP with an accuracy of up to 0.93 [95%-CI: 0.91–0.94]. Discussion: Our study shows that mitochondrial dysfunction and bioenergetic depletion contribute to idiopathic Parkinson disease pathophysiology but not to progressive supranuclear palsy. Combined morphometric and metabolic imaging could serve as an accompanying diagnostic biomarker in the neuroimaging-guided differential diagnosis of these parkinsonian disorders. Classification of Evidence: This study provides Class III evidence that 31 phosphorus magnetic resonance spectroscopy imaging combined with morphometric MRI can differentiate PwPD from PwPSP.